A computational fluid dynamics analysis of a patient with acute non-A-non-B aortic dissection after type I hybrid arch repair. (March 2020) - Xiong, Zhuxiang; Yang, Peng; Li, Da; Qiu, Yue; Zheng, Tinghui; Hu, Jia
Highlights: Type I hybrid arch repair is an effective treatment option for non-A-non-B aortic dissection. The short-term outcome of this particular patient is satisfactory after hybrid arch repair. The hemodynamic parameters become normal after hybrid arch repair. Abstract: The clinical presentation and natural courses in acute non-A-non-B aortic dissection (AD) are quite different from classical acute type A or type B AD, and the benefit of hybrid technique for this clinical scenario has not been validated. By using computational fluid dynamics (CFD) analysis, we aim to investigate a series of hemodynamic-related changes in aortic morphology in a patient who underwent type I hybrid arch repair (HAR). Computed tomographic angiographies (preoperative, one week, one month and one year after HAR) of a 52-year old male patient with arch-entry type acute non-A-non-B dissection were collected. Three-dimensional models were reconstructed by using an image processing package Mimics (materialize). Morphological and hemodynamic parameters of aorta and its branch vessels were analysed. Post-operatively, the false lumen index (FLI) gradually decreased from 2.02 to 0.38 and the curvature of the aortic arch was also reduced. However, the aortic arch lengthened and the diameter of the distal abdominal aorta expanded. In addition, the blood flow gradually became organised and the pressure in the true lumen (TL) increased over time and eventually approximated the pressure in the false lumen (FL). Moreover, the region of the abnormal wall shear stress (WSS) in the TL progressively decreased while the WSS in most areas of the FL remained below 4 dyne/cm 2 . The blood supply to most of the aortic branches returned to normal at the one-year follow-up. Type I HAR is an effective procedure for patients with acute non-A-non-B aortic dissection in terms of restoring normal blood flow in TL and facilitating positive remodeling of distal aorta. Long-term surveillance and follow-up is mandatory.